THE INFLUENCE OF CSR STRATEGY EVALUATION ON SUSTAINABLE COMMUNITY DEVELOPMENT - Aisyah, Nur; Rismawati, Rismawati; Rahmawati, Rahmawati (ITB AAS Indonesia Surakarta, 2024)
Abstract This study pursues two objectives. Firstly, it seeks to ascertain how Corporate Social Responsibility (CSR) is defined and secondly, it aims to understand to what extent CSR plays a role in generating positive impacts on sustainable development, as well as to provide deep insights on effective strategies. Employing a quantitative method, this study evaluates CSR strategies and their impacts sustainable community development. The population of this study comprises all employees at PT PLN (Persero) UP3 Palopo involved in the CSR program, with a sample size of 100 respondents. The findings suggest that based on the statistical analysis conducted, there is no strong evidence supporting a positive and significant evaluation on sustainable development within the research framework employed in this study. This indicates that other factors may have a more dominant role in influencing sustainable development, or further research may be needed with a different framework to understand the relationship between these variables Kata kunci: CSR (Corporate Social Responsibility), Evaluation, Social Inclusion, Sustainable Community Development.